PENINGKATAN HILIRISASI KOPI MELALUI PELATIHAN DAN INOVASI TEKNOLOGI BAGI KELOMPOK TANI BUKIK GOMPONG DI NAGARI KOTO GADANG GUGUK KABUPATEN SOLOK - Tivany Edwin; Tevina Edwin; Nuzulia Irawati; Putri Gemala Sari; Veri Syah Putra; Fajrul Ikhsan (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Every year, the Bukik Gompong Organic Garden farmer group produces around 13 tons of coffee cherries along with waste in the form of coffee husks/cascara. The processing of coffee cherries into green beans is often delayed due to unstable weather conditions, which prolongs the drying process. In addition, the absence of roasting machines means that once the green beans are produced, they have to be roasted in Padang City, which is both time-consuming and costly. The farmers' group has not directly witnessed the coffee processing products consumed by the public, so a comparative study is needed to motivate them to produce high-quality coffee cherries. Therefore, the community service method in this study involves conducting a benchmarking study for the farmers' group to Rimbun Roastery in Padang City, providing short training on coffee cupping and roasting, assisting in the procurement of equipment for coffee drying using coffee husk waste, and the procurement of coffee roasting equipment.. The results of the community service initiative show that the farmers' group has benefited from the coffee taste testing and roasting training activities. The group has also gained an understanding that higher quality coffee commands higher prices, thereby motivating the farmers to produce high-quality coffee. Similarly, the provision of coffee drying equipment and roasting machines has benefited the farmers' group in terms of time and cost efficiency in coffee production. This community service activity has proven to have a positive impact on the Bukik Gompong farmer group.